Considerations in the treatment of the patient with epilepsy. A review article - Juan E. Bender del Busto; Liuba Hernández Toledo (Universidad de Ciencias Médicas de La Habana, 2018)
Introduction: Epilepsy is as old as mankind, and for some people, the second neurological disease.  It has gone through different cultures and epochs, following different treatments until the 19th century when the scientific and modern therapy began, which currently maintains in absolute development. Objective: To present and reflect on the use of antiepileptic drugs described up to the present, the ones which are under investigation, and the future development trends. Material and Method:  A bibliographic review was performed by searching different online databases, related to antiepileptic therapy.  The reports of original prospective or retrospective researches, and review works were included in the information search.  The 79-year period reviewed extended from 1937 to 2016. Results: The importance of the positive diagnosis of epilepsy for a correct management of the patient is described. Antiepileptic treatment is approached, with a specificity on the drugs described up to the present time, the ones that are under complete development, and the general principles of treatment and worries in the field of neurosciences, with a view to achieve an efficient therapy. Conclusions: The current antiepileptic therapy is symptomatic and not curative, being necessary to keep in mind the general aspects in the management of the epileptic patient, in an integral and individualized way. Keywords: epilepsy, scientific therapy, antiepileptic drugs.